Trajectoires de transition écologique (éditions Quae, 2024)
Floods, heatwaves, fires and other extreme weather events are all in the news. Their frequency, duration and intensity are accelerating as a result of climate change. Local and regional authorities are in the front line, and must lead the ecological transition to mitigate the causes and adapt to them. Given the scope of their responsibilities in terms of regional planning, economic development, transport, housing, etc., 15% of greenhouse gas emissions (and indirectly 50%) can be attributed to their decisions. Their involvement is therefore crucial if we are to achieve carbon neutrality and adapt to climate change. It is aimed at local authorities and regional planning stakeholders, and aims to bring the academic world closer to public policy professionals. Planning can and must encourage the development of multiple and differentiated "ecological transition trajectories", taking account of specific territorial characteristics. But what is a trajectory? Is contemporary planning adapted to the issues at stake? How can we move towards more 'dynamic' and 'adaptive' planning of territories in order to respond to ecological temporalities? This book provides background information, examples and methodologies of trajectories tested in different regions, to shed light on territorial planning in the context of the ecological transition and to stimulate reflection on these issues. It is aimed at local authorities and regional planning stakeholders, and aims to bring the academic world closer to public policy professionals.